Treatment of COVID-19 with Herbal Medicines: Perceptions, Attitudes and Practices of Healthcare Professionals Students in Uganda - Kiyimba, Blaise; Kanyike, Andrew Marvin; Ssewante, Nelson; Musoke, Phillip; Atulinda, Linda; Namuwaya, Claire; Wamala, Nicholas Kisaakye; Onyait, Teddy; Aringo, Ramona Noeline; Kato, Hussein; Asasira, Ignatius; Bongomin, Felix (ResearchSquare, 2021)
Use of herbal medicine (HM) for the treatment and prevention of the coronavirus disease -2019 (COVID19) has been reported worldwide. In this study, we aimed to assess the perceptions, attitude and practices of healthcare professionals (HP) students in Uganda concerning HM use in the management of COVID-19 illness
Keywords: Herbal medicine; COVID-19; Treatment; Healthcare; Students